Right to be hostile : schools, prisons, and the making of public enemies - Meiners, Erica R. (Routledge, 2007)
Offers examples and insights into the "school to prison' pipeline phenomenon, showing how disciplinary regulations, pedagogy, pop culture and more not only implicitly advance, but actually normalize an expectation of incarceration for urban youth.